Produktivitas Dan Pendapatan Usahatani Jagung di Desa Sukanalu, Kecamatan Barus Jahe, Kabupaten Karo - Maryanti Sitohang; Tambunan, Herlina Yolanda (JURNAL AGRIUST, 2025)
Corn is one of the agricultural sector food crop commodities that is widely cultivated by farmers in Indonesia. Corn is included in the group of National food ingredients which is positioned as the main staple food after rice so that it is called a buffer for National food security. This study aims to analyze the productivity and income of corn farming / Ha / MT in Sukanalu Village, Barus Jahe District. The research methods used are observation, interviews and questionnaires. The data analysis used is productivity and income analysis. The results of the study showed that the productivity of corn farming in Sukanalu Village, Barus Jahe District was 7.7 tons / / Ha / MT and the level of net income of corn farming for an average per hectare of Rp 20,296,666 / ha / planting season.